A microwave-assisted and efficient reduction protocol for the synthesis of alkyl-substituted [2.2]-paracyclophanes. Issue 2 (April 2023) - Tian, Mengyuan; Zhang, Lixiang; Gao, Lijing; Xiao, Guomin
[2.2]-Paracyclophane derivatives have been promising platforms for applications in biology and materials science. To access pure derivatives thereof, a safe and non-toxic synthetic method for 4- n -propyl-[2.2]-paracyclophane is developed via a microwave-assisted and NH2 NH2 /KOH reduction route. We introduce microwave-assisted acylation for a synthesis that successfully improves the yield and reduces the reaction time. Notably, an exploration of the length and number of the alkyl chains on the [2.2]-paracyclophane ring did not significantly affect the outcome of this reaction. We synthesized 4- n -butyl-[2.2]-paracyclophane and 4, 12-dipropyl-[2.2]-paracyclophane via our protocol with high yields. The regioselectivity of the second electrophilic substitution on 4- n -propyl-[2.2]-paracyclophane occurs at the para position of the less substituted phenyl ring.